Applying PQ4R Strategy for Teaching Reading - Moh Rodli (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2015)
Despite receiving more attention than other language skills in English classroom, the result of students’ reading comprehension achievement is still far from expectation. To help students comprehend English reading texts and have better achievement in reading skill, PQ4R strategy can be an alternative to offer. The PQ4R (also well known as SQ4R) strategy of comprehending reading material is an extension of SQ3R (Survey, Question, Read, Recite, and Review) This method involves previewing the reading material, questioning the reading, reading to answer the questions, reflecting upon the reading, reciting the reading, and reviewing the material. This method is useful for improving students’ reading effectiveness in addition to help students better remember what they read. This paper highlights the PQ4R strategy and its use as an alternative to improve students’ reading comprehension achievement.